PENAMBAHAN TEPUNG BIJI DURIAN (Durio zibethinus Murr) DALAM PEMBUATAN ROTI TAWAR - S, Ryan Nathanael; Efendi, Raswen '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to obtain the best ratio of durian seed flour and wheat flour to produce a good quality white bread. This research was carried out experimentally by using completely randomized design (CRD) with five treatments and four replications in order to obtain tweenty experiments unit. Analysis of variance showed that the ratio of the addition of durian seed flour and wheat flour significantly effect on moisture content, ash content, protein content, fatÂ  content, carbohydrate content, bread improver, descriptive sensory assessment on the parameters of colour, aroma and texture as well as hedonic sensory assessment on parameters of colour and aroma. White bread best treatment according to chemical analysis and sensory assessment is descriptive and hedonic P2 treatment which has moisture content of 27.53%, ash content of 1.65%, protein content of 13.46%, fat content of 5.28%, carbohydrate content of 52.08%, and bread improver of 222.50%. Â  Keywords : Durian seed flour, wheat flour, white bread.